QUALITY ASSESSMENT OF DIFFERENT BRANDS OF PACKAGED DRINKING WATER AVAILABLE IN INDIAN MARKET - Alok M1, Babita M3Versha P1, Dharmender K1 Vibhu P2 (Journal of Biomedical and Pharmaceutical Research, 2017)
Objective: Water makes up more than two thirds of the weight of the human body. Water is important in homeostasis process to maintain the relatively constant temperatures within the body 80% of the diseases in India are water-borne. The exploration, exploitation and unscientific management of water resources in Dehradun have posed a serious threat of reduction in usage of this supply for drinking purpose thus leading to increased consumption of packaged drinking water. Method: In present study five brands of packaged drinking water bottles sold in the market of Dehradun city of Uttarakhand were taken and analysed for quality parameters. Physical (colour, odour, taste, temperature conductivity etc.) chemical (hardness, tds tss, total alkalinity, cod, bod etc) and microbiological characteristics (colony count) of these brands were studied and compared to Dehradun supply water on the same lines. Studies were repeated to come to concurrent conclusion. Results: Present study results showed that physical and chemical characteristics of the brands fulfill all the requirements and comply all standard values in comparison to water supply sample which was found to be unsafe for drinking purpose .Further All the brands were also tested for colony count for bacteria in bottles after 24 and 48 hrs of opening of the bottles. Conclusion: All brands of packaged drinking water bottles sold in Dehradun city of Uttarakhand are reported to be safe to use in comparison to water supply sample of the city. Keywords: Contamination, insecticides, pesticides and mineral bottled